Applied ethics in the fractured state - Grant, Bligh; Drew, Joseph S. (Political scientist); Christensen, Helen E. (Research in ethical issues in organizations ;, 2018)
This book brings together the refereed proceedings of the 24th Annual Conference of the Australian Association of Professional and Applied Ethics (AAPAE) 'Applied Ethics in the Fractured State', held at the Institute for Public Policy and Governance, University of Technology Sydney in June 2017. The book is eclectic, with chapters on health regulation in Australia, Eastern ethical theorising (Confucianism; Buddhism), euthanasia and community engagement, all of which are examined from the unique perspective that Research in Ethical Issues in Organizations affords its contributors.